Electrode film and preparation method and application thereof
By adjusting the composition and structure of the electrode film, improving fibrosis and reducing the content of binder, a specific preparation process is adopted to solve the problems of high energy consumption and poor tensile strength in the preparation of lithium-ion battery electrodes, and the high efficiency of the electrode is achieved Preparation and long-life continuous production.
Patent Information
- Application Number
- CN202310757712.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
AI Technical Summary
In the existing preparation process of lithium-ion battery electrodes, the wet method consumes high energy consumption and high manufacturing cost, while the tensile strength of the electrode film prepared by the dry method is poor, which affects the service life and continuous production of the electrode.
By adjusting the composition and structure of the electrode film, increasing the fibrosis degree and reducing the binder content, the electrode film is prepared by premixing, shearing and rolling treatment to improve the tensile strength and continuous production capacity of the electrode film.
It significantly improves the tensile strength of the electrode film, extends the service life of the electrode, realizes continuous and stable production of the electrode, reduces manufacturing costs, and improves electrochemical performance.
Smart Images

Figure CN119208504A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to an electrode film and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in consumer electronics and electric vehicle products due to their high energy efficiency, environmental friendliness, and high energy density, and have attracted much attention as a key technology for large-scale energy storage systems. Electrodes, as an important component of lithium-ion batteries, have a crucial impact on the performance of lithium-ion batteries. At present, electrodes are mainly prepared by wet methods, and the main steps include: forming a slurry with the active substance and the solvent, setting the slurry on the surface of the current collector, and forming an electrode including an electrode film after drying. However, this method not only has high energy consumption and a long preparation cycle, but also requires the recovery of NMP during the preparation process, which greatly increases the manufacturing cost of lithium-ion batteries.
[0003] In order to simplify the preparation process, reduce energy consumption, and further reduce the manufacturing cost of lithium-ion batteries, the technology of dry preparation of electrodes came into being. Unlike the wet method, no solvent is added during the dry preparation of electrodes. The powders of active materials, conductive agents and binders are directly mixed and rolled into an electrode film, and then the electrode film is compounded with the current collector to obtain an electrode containing an electrode film. However, the tensile strength of the electrode film obtained by the dry preparation is poor, which not only affects the service life of the electrode, but also affects the continuous production of the electrode.
[0004] Therefore, there is an urgent need to provide an electrode membrane with excellent tensile strength that can realize continuous electrode production. Summary of the invention
[0005] The embodiment of the present application provides an electrode membrane, which can significantly improve the tensile strength of the electrode membrane by adjusting the composition and structure of the electrode membrane, thereby increasing the service life of the electrode. In addition, the preparation process of the electrode is simple, continuous production can be achieved, and manufacturing costs can be reduced, thus having strong application value.
[0006] The embodiment of the present application provides a method for preparing an electrode film, which can prepare the above-mentioned electrode film, and has a simple preparation process and low energy consumption, which helps to save manufacturing costs.
[0007] An embodiment of the present application provides an electrode, which includes the above-mentioned electrode film, so its preparation process is simple, continuous production can be achieved, and the manufacturing cost is low.
[0008] An embodiment of the present application provides an electrochemical device, which includes the above-mentioned electrode, so the electrochemical device has a longer service life and lower production cost.
[0009] An embodiment of the present application provides an electronic device, which includes the above-mentioned electrochemical device, so the electronic device has a longer service life and lower production cost.
[0010] The present application provides an electrode membrane, wherein the electrode membrane comprises fibers, and the fiberization degree of the electrode membrane is 40-95%;
[0011] Based on the total mass of the electrode film, the mass percentage of the binder is ≤2%.
[0012] The electrode membrane as described above, wherein the fibers include first fibers and second fibers, the length of the first fibers is less than or equal to the particle size of the active material, and the length of the second fibers is greater than the particle size of the active material.
[0013] The electrode membrane as described above, wherein the amount percentage of the first fibers in the fibers is 5-50%.
[0014] The electrode membrane as described above, wherein the length of the first fibers is 0.3-10 μm;
[0015] And / or, the second fibers have a length of 50-300 μm.
[0016] The electrode membrane as described above, wherein the diameter of the first fibers and / or the second fibers is 60-150 nm.
[0017] The electrode film as described above, wherein the thickness of the electrode film is 110-2000 μm.
[0018] The electrode film as described above, wherein the active material is selected from at least one of carbon materials, metal platinum, silicon-carbon materials, lithium iron phosphate materials, positive electrode ternary materials, silicon-oxygen materials, lithium cobalt oxide, lithium manganese oxide and lithium titanate.
[0019] The electrode membrane as described above, wherein the length of the first fibers is 0.3-3 μm, 0.3-5 μm, 5-10 μm or 3-10 μm.
[0020] The electrode membrane as described above, wherein the length of the second fibers is 50-200 μm, 100-150 μm, 150-200 μm or 200-300 μm.
[0021] The electrode film as described above, wherein the thickness of the electrode film is 110-500 μm, 110-300 μm, 100-350 μm, 110-500 μm, 500-800 μm, 500-1000 μm or 1000-2000 μm.
[0022] The electrode membrane as described above, wherein the fiberization degree of the electrode membrane is 60-90%, 50-70%, 70-95% or 40-60%.
[0023] The electrode film as described above, wherein the mass percentage of the binder is 1%, 1.3%, 1.5%, 1.8% or 2% based on the total mass of the electrode film.
[0024] The present application provides a method for preparing the electrode film as described above, which comprises:
[0025] The raw material system including the conductive agent, the binder and the active material is sequentially subjected to premixing treatment, shearing treatment and roll pressing treatment to obtain the electrode film;
[0026] Wherein, in the raw material system, the mass percentage of the binder is ≤2%, and the binder includes a fibrillable binder;
[0027] In the premixing process, the speed is 1000-3000 r / min, the temperature is 18-30° C., and the time is 2-60 min;
[0028] In the shearing treatment, the rotation speed is 5000-7000 r / min, the temperature is 10-90° C., and the time is 5-90 min.
[0029] The present application provides an electrode, which includes the electrode film as described above.
[0030] The present application provides an electrochemical device, which includes the electrode as described above.
[0031] The present application provides an electronic device, wherein a driving source or an energy storage source of the electronic device includes the electrochemical device as described above.
[0032] The electrode membrane provided in the embodiment of the present application includes fibers, the fiberization degree of the electrode membrane is 40-95%, and the mass percentage of the binder in the electrode membrane is ≤2%. The electrode membrane of the present application has a high fiberization degree, so the binder chain is fully expanded and has excellent adhesion. Therefore, it can fully bond other substances (for example, active substances, conductive agents) in the electrode membrane while reducing the amount of binder added, thereby improving the tensile strength of the electrode membrane and thus improving the service life of the electrode. And because the electrode membrane has excellent tensile strength, its production process is not easy to break, and continuous and stable production can be achieved, reducing manufacturing costs; due to the reduction in the binder content, the content of active substances in the electrode membrane can be increased, so the electrode membrane of the present application can also improve the electrochemical performance of the electrode.
[0033] The electrode film preparation method provided in the embodiment of the present application can prepare the above-mentioned electrode film, and the preparation method also has the advantages of simple process, low energy consumption, and continuous stability, which is conducive to wide promotion and application.
[0034] The electrode provided in the embodiment of the present application includes the above-mentioned electrode film, so its preparation process is simple, continuous production can be achieved, the manufacturing cost is low, and it has excellent electrochemical properties. When applied to an electrochemical device, it helps to improve the electrochemical performance of the electrochemical device and extend the service life of the electrochemical device.
[0035] The electrochemical device provided in the embodiment of the present application adopts the aforementioned electrode, and therefore has a long service life, a simple manufacturing process, and low preparation cost. In addition, it also has excellent electrochemical properties, such as excellent energy density and rate performance.
[0036] The electronic device provided in the embodiment of the present application has an excellent service life and provides an excellent user experience because it is driven or energy stored by the aforementioned electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present application or related technology descriptions. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 is a SEM image of the electrode film in Example 1 of the present application;
[0039] Figure 2 is a SEM image of the electrode film in Example 2 of the present application;
[0040] Figure 3 is a SEM image of the electrode film in Example 3 of the present application;
[0041] Figure 4 is a SEM image of the electrode film in Example 4 of the present application;
[0042] Figure 5 is a SEM image of the electrode film in Comparative Example 1 of the present application;
[0043] Figure 6 This is a SEM image of the electrode film in Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The terms used in the implementation mode of this application are only used to explain the specific embodiments of the present application, and are not intended to limit the present application. The implementation mode of the embodiments of the present application will be described in detail in combination with the accompanying drawings.
[0045] In order to simplify the preparation process and reduce energy consumption, those skilled in the art use a dry method to prepare electrode membranes.
[0046] For example, CN 112424973A discloses a dry electrode film, and the dry electrode film is obtained by sequentially mixing and calendering a mixture including an active substance, a porous carbon material, and a dry binder. Although this method can obtain a dry electrode film, the bonding degree between the active substances in the obtained dry electrode film is poor, so the tensile strength of the obtained dry electrode film has further room for improvement.
[0047] CN113871566A discloses a dry electrode membrane, and the dry electrode membrane is obtained by sequentially subjecting a mixture including an active substance, a conductive agent and a polymer membrane to a fiberization treatment and a heating and calendering treatment. Although this method can obtain an electrode membrane with fibers, the diameter of the formed fibers is small and the bonding degree is poor, so the tensile strength of the obtained electrode membrane is poor and it is easy to break brittlely. In addition, this method requires the use of a polymer membrane with a specific morphology, has high requirements for raw materials, and has poor applicability.
[0048] Based on the above-mentioned defects, the first aspect of the embodiment of the present application provides an electrode membrane, wherein the electrode membrane includes fibers, and the fiberization degree of the electrode membrane is 40-95%;
[0049] Based on the total mass of the electrode film, the mass percentage of the binder is ≤2%.
[0050] In the present application, the electrode membrane is used to generate an electrochemical reaction, thereby converting chemical energy into electrical energy.
[0051] It can be understood that the electrode film of the present application also includes active substances and conductive agents, wherein the active substances are mainly used to generate electrochemical reactions, and the conductive agents are mainly used to improve the conductivity of the electrode film. The binder of the present application is used to bond the active substances and the conductive agents, so that the active substances and the conductive agents can form a complete electrode film, thereby improving the mechanical properties of the electrode film.
[0052] The binder of the present application at least includes a fibrillable binder. The present application does not particularly limit the fibrillable binder, which can be a fibrillable binder commonly used in the art. Exemplarily, the fibrillable binder can be PTFE. The fiber of the present application refers to continuous or discontinuous filaments. In some embodiments, the fiber is formed by fibrillation of a fibrillable binder. The binder of the present application can also include other binders commonly used in the art, for example, the binder includes but is not limited to one of polyvinylidene fluoride (PVDF) or polyethylene oxide (PEO).
[0053] In the present application, the mass percentage of the binder refers to the mass percentage of the binder in the electrode film in the total mass of the electrode film. In a specific embodiment, the mass percentage of the binder can be the mass percentage of the fibrillable binder.
[0054] The fiberization degree of the electrode membrane refers to the mass percentage of the fibers formed by fibrillation of the fibrillable binder in the fibrillable binder.
[0055] The present application can use the commonly used methods in the art to obtain the fiberization degree of the electrode membrane. In some embodiments, the electrode membrane can be subjected to thermogravimetric analysis to obtain the fiberization degree of the electrode membrane. Specifically, the electrode membrane can be subjected to thermogravimetric analysis using the method disclosed in patent US005686033A to obtain the fiberization degree of the electrode membrane.
[0056] Since the fibrillable binder can form fibers after fibrillation, the electrode membrane including the fibrillable binder has a certain degree of fiberization. Therefore, it can be understood that the higher the degree of fiberization of the electrode membrane, the more fully the binder chains of the fibrillable binder are unfolded, so that other substances in the electrode membrane (such as active substances and conductive agents) can be better bonded; and since the higher degree of fiberization gives the binder excellent bonding properties, the binder content in the electrode membrane can be reduced without affecting the bonding properties of the binder. As the binder content in the electrode membrane decreases, the content of other substances (such as active substances and conductive agents) will increase, thereby helping to improve the electrochemical properties of the electrode membrane. For example, an increase in the content of active substances can increase the energy density of the electrode membrane, and an increase in the content of conductive agents can improve the rate performance of the electrode membrane.
[0057] The fiberization degree of the electrode membrane of the present application is 40-95%. Its high fiberization degree can fully bond other substances in the electrode membrane and reduce the content of the binder in the electrode membrane (reducing the content of the binder to ≤2%). Therefore, the electrode membrane of the present application not only has excellent tensile strength, but is also not easy to break during the production process, and can achieve continuous and stable production, reducing manufacturing costs. In addition, the electrode membrane of the present application also has excellent electrochemical properties.
[0058] In some embodiments, the present application has an electrode membrane with a special composition and structure, the tension of which can be greater than 0.8N and the strength of which can be greater than 1MPa.
[0059] In some embodiments of the present application, the electrode membrane also includes an active substance, the fibers include first fibers and second fibers, the length of the first fibers is less than or equal to the order of magnitude of the particle size of the active substance, and the length of the second fibers is greater than the order of magnitude of the particle size of the active substance.
[0060] In some embodiments, a SEM image of the electrode film can be obtained, and the SEM image of the electrode film can be analyzed using image analysis software commonly used in the field to obtain the length of each fiber in the electrode film, and then the fibers are divided into first fibers and second fibers according to the size relationship between the order of magnitude of the length of each fiber and the order of magnitude of the particle size of the active substance in the electrode film. For example, if the order of magnitude of the length of the fiber is less than or equal to the order of magnitude of the particle size of the active substance, the fiber is the first fiber; if the order of magnitude of the length of the fiber is greater than the order of magnitude of the particle size of the active substance, the fiber is the second fiber. In a specific embodiment, the image analysis software can be image-J software.
[0061] The following is an exemplary description of the length of the first fiber and the length of the second fiber. For example, the particle size of the active substance is 5 μm (order of magnitude 1), the length of the first fiber can be 0.1-9 μm (order of magnitude less than or equal to 1), and the length of the second fiber can be ≥10 μm (order of magnitude greater than or equal to 2).
[0062] The present application does not limit the arrangement of the first fiber and the second fiber in the electrode film. The first fiber and the second fiber can be arranged regularly or randomly. The order of magnitude of the length of the first fiber is less than or equal to the order of magnitude of the particle size of the active material, so the first fiber can better achieve close bonding between two adjacent active materials and improve the cohesion of the electrode film. The order of magnitude of the length of the second fiber is greater than the order of magnitude of the particle size of the active material, so the second fiber can better achieve close bonding of multiple active materials in the horizontal or vertical direction and improve the overall tensile strength of the electrode active layer.
[0063] Therefore, the electrode membrane of the present application has excellent tensile strength, is not easy to break during the production process, can achieve continuous and stable production, and reduces manufacturing costs.
[0064] In some embodiments of the present application, the amount percentage of the first fibers in the fibers is 5-50%.
[0065] In the present application, the number percentage of the first fiber in the fiber refers to the number percentage of the first fiber based on the total number of fibers. Exemplarily, the number percentage of the first fiber in the fiber can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two thereof.
[0066] It can be understood that when the percentage of the first fibers in the fibers is 5-50%, the percentage of the second fibers in the fibers is 50-95%.
[0067] In some embodiments, the SEM image of the electrode film can be analyzed using image analysis software commonly used in the art to obtain a distribution curve of the fibers in the electrode film, and the number percentage of the first fibers can be obtained based on the distribution curve. In a specific embodiment, the image analysis software can be image-J software.
[0068] When the number percentage of the first fibers is 5-50%, the first fibers and the second fibers can be better matched, wherein the first fibers can better achieve the bonding between two adjacent active substances, further improving the cohesion of the electrode membrane, and the second fibers can better achieve the lateral or longitudinal bonding of the active substances, thereby further improving the mechanical properties of the electrode membrane.
[0069] In some embodiments, when the amount percentage of the first fibers in the fibers is 20-35%, the obtained electrode film has more excellent mechanical properties (eg, tension, elasticity).
[0070] In some embodiments of the present application, the length of the first fiber is 0.3-10 μm;
[0071] And / or, the second fibers have a length of 50-300 μm.
[0072] In the present application, when the length of the first fiber meets 0.3-10 μm, it can better match the particle size of the active material, tightly bond two adjacent active materials, and improve the cohesion of the electrode film. When the length of the second fiber meets 50-300 μm, it can further improve the overall tensile strength of the electrode film without affecting the electrochemical properties of the electrode film.
[0073] In some embodiments of the present application, the diameter of the first fiber and / or the second fiber is 60-150 nm.
[0074] The diameter of the first fiber and / or the second fiber refers to the average size of the first fiber and / or the second fiber in a direction perpendicular to the length. For example, the diameter of the first fiber can be 60 nm, 100 nm, 150 nm, or a range consisting of any two thereof; the diameter of the second fiber can be 60 nm, 100 nm, 150 nm, or a range consisting of any two thereof.
[0075] When the diameters of the first fibers and / or the second fibers satisfy the above relationship, the tensile strength of the electrode membrane can be further improved without affecting the electrochemical properties of the electrode membrane, thereby extending the service life of the electrode.
[0076] In practical applications, the thicker the electrode film, the worse its tensile properties and the easier it is to break. The present application enables the thicker electrode film to still have excellent tensile properties by making the electrode film have a higher degree of fiberization, so that the electrode film is not likely to break during processing or use.
[0077] In some embodiments of the present application, the electrode film can have an excellent tensile strength when the thickness is 110-2000 μm, and as the thickness of the electrode film increases, the content of active substances in the electrode film will also increase significantly, which helps to improve the energy density of the electrode film, thereby obtaining an electrochemical device with excellent energy density.
[0078] In some embodiments, the driving range of electronic devices including the electrochemical device is significantly improved, and the service life is significantly extended. For example, the driving range can be increased by 20-30%, and the service life can be extended by 5-8%.
[0079] The present application does not specifically limit the conductive agent in the electrode film, and the conductive agent may be a conductive agent commonly used in the art. The conductive agent may be at least one of a zero-dimensional conductive agent, a two-dimensional conductive agent, and a three-dimensional conductive agent. Specifically, the conductive agent may be selected from but not limited to at least one of super-P, conductive carbon black, carbon nanotubes, and acetylene black.
[0080] The present application does not particularly limit the active material in the electrode membrane, and active materials commonly used in the art may be selected, for example, lithium ion battery positive electrode active materials, lithium ion battery negative electrode active materials, hydrogen fuel cell active materials or supercapacitor active materials.
[0081] Specifically, the active material can be a carbon material, metal platinum, silicon-carbon material, silicon nitride, lithium iron phosphate material, positive electrode ternary material, silicon-oxygen material, lithium cobalt oxide, lithium manganese oxide or lithium titanate.
[0082] The carbon material may be at least one of artificial graphite, natural graphite and mesophase carbon microspheres;
[0083] Silicon-carbon materials refer to materials containing silicon and carbon, such as SiC;
[0084] The lithium iron phosphate material may be LiFePO4;
[0085] The positive electrode ternary material refers to a positive electrode ternary material including Ni, Co and Mn, for example, polycrystalline NCM811, single crystal NCM811 or NCM721;
[0086] Silicon-oxygen materials refer to materials containing silicon and oxygen, such as SiOx.
[0087] The length of the first fiber of the present application may be 0.3-3 μm, 0.3-5 μm, 5-10 μm or 3-10 μm.
[0088] Illustratively, the length of the first fiber may be 0.3 μm, 1 μm, 1.5 μm, 2 μm, 2.2 μm, 3.2 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, or a range consisting of any two thereof.
[0089] The length of the second fiber of the present application may be 50-200 μm, 100-150 μm, 150-200 μm or 200-300 μm.
[0090] Illustratively, the length of the second fiber may be 50 μm, 70 μm, 80 μm, 100 μm, 125 μm, 150 μm, 180 μm, 200 μm, 250 μm, 300 μm, or a range consisting of any two thereof.
[0091] The thickness of the electrode film of the present application may be 110-500 μm, 110-300 μm, 100-350 μm, 110-500 μm, 500-800 μm, 500-1000 μm or 1000-2000 μm.
[0092] Illustratively, the thickness of the electrode film may be 110 μm, 200 μm, 250 μm, 300 μm, 350 μm, 500 μm, 700 μm, 1000 μm, 1500 μm, 2000 μm, or a range consisting of any two thereof.
[0093] The fiberization degree of the electrode membrane of the present application may be 60-90%, 50-70%, 70-95% or 40-60%.
[0094] Furthermore, the fiberization degree of the electrode membrane may be 40%, 45%, 50%, 55%, 60%, 70%, 75%, 85%, 90%, 95% or a range consisting of any two thereof.
[0095] In the present application, based on the total mass of the electrode film, the mass percentage of the binder is 1%, 1.3%, 1.5%, 1.8% or 2%.
[0096] It is understandable that the above parameters (for example, the length of the first fiber, the length of the second fiber, the fiberization degree of the electrode membrane, the thickness of the electrode membrane or the mass percentage of the binder) may have measurement errors when measuring, and the existence of measurement errors does not affect the scope of protection of this application.
[0097] In practical applications, parameters such as the length of the first fiber, the length of the second fiber, the fiberization degree of the electrode membrane, and the thickness of the electrode membrane can be matched according to different active materials, so that the electrode membrane has better electrochemical and mechanical properties, thereby improving the overall performance of the electrochemical device.
[0098] The second aspect of the embodiment of the present application provides a method for preparing an electrode film, comprising: sequentially performing premixing, shearing and rolling treatments on a raw material system including a conductive agent, a binder and an active material to obtain an electrode film.
[0099] Wherein, in the raw material system, the mass percentage of the binder is ≤2%, and the binder includes a fibrillating binder;
[0100] In the premixing process, the speed is 1000-3000r / min, the temperature is 18-30℃, and the time is 2-60min;
[0101] During the shearing process, the rotation speed is 5000-7000 r / min, the temperature is 10-90° C., and the time is 5-90 min.
[0102] Specifically, in the premixing process, the rotation speed may be 1000 r / min, 1500 r / min, 1700 r / min, 2000 r / min, 2500 r / min or 3000 r / min;
[0103] The temperature may be 18°C, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C or a range consisting of any two thereof;
[0104] The time may be 2 min, 10 min, 15 min, 20 min, 25 min, 30 min, 40 min, 45 min, 50 min, 55 min, 60 min or a range consisting of any two thereof;
[0105] During the shearing process, the rotation speed may be 5000 r / min, 5500 r / min, 6000 r / min, 6500 r / min, 7000 r / min or a range consisting of any two thereof;
[0106] The temperature may be 10°C, 15°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or a range consisting of any two thereof;
[0107] The time can be 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 40 min, 45 min, 50 min, 55 min, 60 min, 70 min, 80 min, 90 min or a range consisting of any two of them.
[0108] The preparation method of the electrode membrane of the present application specifically includes: premixing a raw material system including a conductive agent, a specific content of a binder and an active substance at a temperature of 18-30°C and a rotation speed of 1000-3000r / min for 2-60min, so that the conductive agent, the binder and the active substance can be evenly mixed; then, at a temperature of 10-90°C, shearing the raw material system after the premixing treatment at a rotation speed of 5000-7000r / min, so that the molecular chains of the fibrillated binder in the binder are fully unfolded to form fibers, and the formed fibers can fully bond the active substance and the conductive agent; finally, rolling treatment is performed to obtain an electrode membrane of target thickness.
[0109] The present application does not impose any specific limitation on the premixing process, as long as the above-mentioned rotation speed, temperature and time are met. In some embodiments, the premixing process can be performed in a blender.
[0110] The present application does not impose any specific limitation on the shearing process, as long as the above-mentioned rotation speed, temperature and time are met. In some embodiments, the shearing process can be performed in a shearing machine.
[0111] The present application does not specifically limit the roller pressing process, and the roller pressing process commonly used in the art may be used.
[0112] In the preparation method of the electrode membrane of the present application, the raw material system including the conductive agent, the fibrillable binder and the active material is premixed by a specific process, so that the conductive agent, the fibrillable binder and the active material can be fully mixed, which is helpful for the subsequent shearing treatment; then the premixed raw material system is sheared by a specific process, so that the premixed raw material system can be fully fibrillated, thereby obtaining an electrode membrane with a high degree of fiberization. The preparation method is simple in process and suitable for wide promotion and application. In addition, the preparation method has high applicability and is suitable for fibrillated binders of various sizes and types.
[0113] A third aspect of an embodiment of the present application provides an electrode, comprising the electrode film of the first aspect.
[0114] The present application does not impose any particular limitation on the electrode, and the electrode may be an electrode of various electrochemical devices, for example, the electrode may be a positive electrode or a negative electrode of a lithium ion battery.
[0115] In a possible implementation, the positive electrode of the lithium-ion battery includes an electrode film disposed on at least one surface of a positive electrode current collector. Specifically, the electrode film is compounded with at least one surface of a positive electrode current collector to obtain a positive electrode of the lithium-ion battery. The active material in the electrode film may be selected from but not limited to at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate. The compounding may be thermal compounding.
[0116] The present application does not particularly limit the positive electrode current collector, and it can be a positive electrode current collector commonly used in the art, such as aluminum foil.
[0117] In a possible implementation, the negative electrode of the lithium-ion battery includes an electrode film disposed on at least one surface of the negative electrode current collector. Specifically, the electrode film is compounded with at least one surface of the negative electrode current collector to obtain the negative electrode of the lithium-ion battery. The Martian material in the electrode film can be selected from at least one of graphite and silicon. The compounding can be thermal compounding.
[0118] The present application does not particularly limit the negative electrode current collector, and it can be a negative electrode current collector commonly used in the art, such as copper foil.
[0119] In some embodiments, the active material is graphite, the negative electrode active material of a lithium-ion battery. The electrode membrane of the present application can realize the gradient preparation of the graphite negative electrode, so that the battery has both high energy density and fast charging performance. When used in new energy vehicles, mobile phones and other scenarios, the charging time can be greatly shortened, for example, the charging time can be shortened from 1 hour to 20 to 15 minutes.
[0120] Since the electrode of the present application includes the electrode film of the first aspect, the electrode not only has excellent tensile force and strength, and is not easily damaged during long-term use, but also has a simple preparation process, can achieve continuous production, and helps to reduce manufacturing costs. At the same time, the electrode of the present application also has excellent electrochemical properties and is suitable for wide promotion and application.
[0121] A fourth aspect of the present application provides an electrochemical device, comprising the electrode film of the first aspect or the electrode of the third aspect.
[0122] The present application does not specifically limit the electrochemical device, and the electrochemical device may be a lithium-ion battery, a hydrogen fuel cell, a flexible solar cell or a supercapacitor.
[0123] Exemplarily, a lithium-ion battery can be prepared by a method comprising the following steps: stacking the positive electrode sheet obtained in the third aspect and the negative electrode sheet obtained in the third aspect to obtain an electrode assembly, with a separator disposed between the positive electrode sheet and the negative electrode sheet; placing the electrode assembly in an outer package, injecting an electrolyte into the outer package, and sealing to obtain a lithium-ion battery;
[0124] The diaphragm may be a commonly used diaphragm in the art. In a possible implementation, the diaphragm may be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride;
[0125] The electrolyte may be a lithium-ion battery electrolyte commonly used in the art. In a possible implementation, the electrolyte includes at least an organic solvent and a lithium salt. The organic solvent may be selected from at least one of ethylene carbonate, butylene carbonate, propylene carbonate, ethyl methyl carbonate, vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, difluoroethylene carbonate, fluorodimethyl carbonate, dimethyl carbonate, diethyl carbonate, and dipropyl carbonate; the lithium salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI);
[0126] The outer packaging may be the outer packaging commonly used in the art.
[0127] When the active material is a carbon material and / or metal platinum, it can be used to prepare a hydrogen fuel cell, and the obtained hydrogen fuel cell can be used in an aqueous environment;
[0128] When the active material is activated carbon, it can be used to prepare supercapacitors in combination with acetonitrile-quaternary ammonium salt electrolyte;
[0129] When the electrode film is at least one of a hole transport layer, an electron blocking layer and a photosensitizing layer, it can be used to prepare a flexible solar cell.
[0130] The electrochemical device of the present application uses the aforementioned electrode membrane or electrode, and therefore has the advantages of a long service life and excellent energy density, as well as a simple manufacturing process and low preparation cost.
[0131] A fifth aspect of the present application provides an electronic device, wherein a driving source or an energy storage source of the electronic device includes the electrochemical device of the fourth aspect.
[0132] Among them, electronic devices may include but are not limited to mobile phones, tablet computers, laptops, ultra-mobile personal computers (UMPCs), handheld computers, walkie-talkies, netbooks, POS machines, personal digital assistants (PDAs), wearable devices, virtual reality equipment, base station power supplies, energy storage power stations, new energy vehicles, trams, high-speed rail emergency power supplies, UPS power supplies, flexible wearable devices and other mobile or fixed terminals with batteries.
[0133] The electronic device of the embodiment of the present application uses the aforementioned electrochemical device as a driving source or energy storage unit, so it has excellent service life and high user satisfaction. In particular, the electrode film of the present application has excellent stretchability, which can improve the flexibility of the electrochemical device and can be widely used in the fields of flexible wearables and flexible screens.
[0134] In some embodiments, the battery life of a base station power supply including the electrochemical device of the present application can be significantly increased; the storage capacity of an energy storage power station including the electrochemical device of the present application can be significantly increased, and the increase in unit storage capacity can reduce the footprint of the energy storage power station; new energy vehicles including the electrochemical device of the present application have excellent battery life; and smartphones including the electrochemical device of the present application have excellent battery life and a long service life.
[0135] The following is a detailed introduction to the embodiments of the present application through specific examples.
[0136] Example 1
[0137] The electrode film of this embodiment is prepared by a method comprising the following steps:
[0138] The raw material system including the conductive agent SP, the binder PTFE, and the active material SiOx-C is sequentially subjected to premixing treatment, shearing treatment, and rolling treatment to obtain an electrode film;
[0139] Among them, in the premixing treatment, the speed was 2000r / min, the temperature was 24℃, and the time was 31min;
[0140] During the shearing treatment, the rotation speed was 6000 r / min, the temperature was 50 °C, and the time was 47 min;
[0141] The thickness of the electrode film is 120 μm, and the mass ratio of SiOx-C, SP and PTFE in the electrode film is 95:3:2;
[0142] The electrode membrane is subjected to SEM testing to obtain a SEM image of the electrode membrane. The SEM image of the electrode membrane is analyzed using image analysis software image-J to obtain the length of the first fiber, the length of the second fiber, the diameter of the first fiber, the diameter of the second fiber, and the percentage of the first fiber in the fiber. Figure 1 is a SEM image of the electrode film in Example 1 of the present application. Figure 1 The analysis shows that the length of the first fiber is 5-10 μm, the length of the second fiber is 150-200 μm, the diameter of the first fiber is 60-150 nm, the diameter of the second fiber is 60-150 nm, and the percentage of the first fiber in the fiber is 25%;
[0143] Thermogravimetric analysis of the electrode membrane was performed according to the method disclosed in patent US005686033A, and the fiberization degree of the electrode membrane was obtained to be 80%.
[0144] Example 2
[0145] The electrode film of this embodiment is prepared by a method comprising the following steps:
[0146] The raw material system including the conductive agent SP, the binder PTFE, and the active material LFP is sequentially subjected to premixing treatment, shearing treatment, and rolling treatment to obtain an electrode film;
[0147] Among them, in the premixing treatment, the speed was 2000r / min, the temperature was 24℃, and the time was 31min;
[0148] During the shearing treatment, the rotation speed was 6000 r / min, the temperature was 50 °C, and the time was 47 min;
[0149] The thickness of the electrode film is 120 μm, and the mass ratio of LFP, SP and PTFE in the electrode film is 96:2:2;
[0150] The electrode membrane is subjected to SEM testing to obtain a SEM image of the electrode membrane. The SEM image of the electrode membrane is analyzed using image analysis software image-J to obtain the length of the first fiber, the length of the second fiber, the diameter of the first fiber, the diameter of the second fiber, and the percentage of the first fiber in the fiber. Figure 2 is a SEM image of the electrode film in Example 2 of the present application. Figure 2 The analysis shows that the length of the first fiber is 0.3-5 μm, the length of the second fiber is 150-200 μm, the diameter of the first fiber is 60-150 nm, the diameter of the second fiber is 60-150 nm, and the percentage of the first fiber in the fiber is 20%;
[0151] Thermogravimetric analysis of the electrode membrane was performed according to the method disclosed in patent US005686033A, and the fiberization degree of the electrode membrane was obtained to be 75%.
[0152] Example 3
[0153] The electrode film of this embodiment is prepared by a method comprising the following steps:
[0154] The raw material system including the conductive agent SP, the binder PTFE, and the active material NCM811 is sequentially subjected to premixing treatment, shearing treatment, and rolling treatment to obtain an electrode film;
[0155] Among them, in the premixing treatment, the speed was 2000r / min, the temperature was 24℃, and the time was 31min;
[0156] During the shearing treatment, the rotation speed was 6000 r / min, the temperature was 50 °C, and the time was 47 min;
[0157] The thickness of the electrode film is 120 μm. In the electrode film, the mass ratio of NCM811 (the mass ratio of single crystal NCM to polycrystalline NCM is 1:1), SP and PTFE is 96:2:2;
[0158] The electrode membrane is subjected to SEM testing to obtain a SEM image of the electrode membrane. The SEM image of the electrode membrane is analyzed using image analysis software image-J to obtain the length of the first fiber, the length of the second fiber, the diameter of the first fiber, the diameter of the second fiber, and the percentage of the first fiber in the fiber. Figure 3 is a SEM image of the electrode film in Example 3 of the present application. Figure 3 The analysis shows that the length of the first fiber is 3-10 μm, the length of the second fiber is 150-200 μm, the diameter of the first fiber is 60-150 nm, the diameter of the second fiber is 60-150 nm, and the percentage of the first fiber in the fiber is 35%;
[0159] Thermogravimetric analysis of the electrode membrane was performed according to the method disclosed in patent US005686033A, and the fiberization degree of the electrode membrane was obtained to be 85%.
[0160] Example 4
[0161] The electrode film of this embodiment is prepared by a method comprising the following steps:
[0162] The raw material system including the conductive agent SP, the binder PTFE, and the active material SiOx is sequentially subjected to premixing treatment, shearing treatment, and roll pressing treatment to obtain an electrode film;
[0163] Among them, in the premixing treatment, the speed was 2000r / min, the temperature was 24℃, and the time was 31min;
[0164] During the shearing treatment, the rotation speed was 6000 r / min, the temperature was 50 °C, and the time was 47 min;
[0165] The thickness of the electrode film is 120 μm, and the mass ratio of SiOx, SP and PTFE in the electrode film is 96:2:2;
[0166] The electrode membrane is subjected to SEM testing to obtain a SEM image of the electrode membrane. The SEM image of the electrode membrane is analyzed using image analysis software image-J to obtain the length of the first fiber, the length of the second fiber, the diameter of the first fiber, the diameter of the second fiber, and the percentage of the first fiber in the fiber. Figure 4 is a SEM image of the electrode film in Example 4 of the present application. Figure 4 The analysis shows that the length of the first fiber is 0.3-3 μm, the length of the second fiber is 80-100 μm, the diameter of the first fiber is 60-150 nm, the diameter of the second fiber is 60-150 nm, and the percentage of the first fiber in the fiber is 20%;
[0167] Thermogravimetric analysis of the electrode membrane was performed according to the method disclosed in patent US005686033A, and the fiberization degree of the electrode membrane was obtained to be 70%.
[0168] Comparative Example 1
[0169] The electrode film of this comparative example is prepared by a method comprising the following steps:
[0170] The raw material system including the conductive agent SP, the binder PTFE and the active material SiOx-C is sequentially subjected to premixing treatment, pulverization treatment and roll pressing treatment to obtain an electrode film;
[0171] Among them, in the premixing process, the speed is 2000r / min;
[0172] The crushing process is carried out in a jet mill, and the crushing time is 1.5 hours;
[0173] The thickness of the electrode film is 120 μm, and the mass ratio of SiOx-C, SP and PTFE in the electrode film is 95:3:2;
[0174] SEM test of the electrode film, Figure 5 is a SEM image of the electrode film in Comparative Example 1 of the present application, such as Figure 5 As shown, there is no obvious filamentous structure in the electrode film in this comparative example, which indicates that air flow pulverization will cause certain damage to the active material and is not conducive to the formation of fibers.
[0175] Thermogravimetric analysis of the electrode membrane was performed according to the method disclosed in patent US005686033A, and the fiberization degree of the electrode membrane was obtained to be 30%.
[0176] Comparative Example 2
[0177] The electrode film of this comparative example is prepared by a method comprising the following steps:
[0178] The raw material system including the conductive agent SP, the binder PTFE and the active material LFP is sequentially subjected to premixing treatment, pulverization treatment and roll pressing treatment to obtain an electrode film;
[0179] Among them, in the premixing process, the speed is 2000r / min;
[0180] The crushing process is carried out in a jet mill, and the crushing time is 1.5 hours;
[0181] The thickness of the electrode film is 120 μm, and the mass ratio of LFP, SP and PTFE in the electrode film is 96:2:2;
[0182] SEM test of the electrode film, Figure 6 is a SEM image of the electrode film in Comparative Example 2 of the present application, such as Figure 6 As shown, the active material in the electrode membrane is obviously broken up, and there is no obvious filamentous structure in the electrode membrane, which indicates that air flow crushing will cause certain damage to the active material and is not conducive to the formation of fibers.
[0183] According to the method disclosed in patent US005686033A, the electrode membrane is subjected to thermogravimetric analysis, and it can be obtained that the fiberization degree of the electrode membrane is 35%.
[0184] Performance Testing
[0185] The tension and pressure test methods described in Parts 7 and 8 of GB / T 1040-92 were used to test the tension and pressure of the electrode membranes in the embodiments and comparative examples, respectively. The test results are shown in Table 1.
[0186] Table 1
[0187] Thickness / μm Tension / N Strength / MPa Example 1 120μm 0.81 1.125 Example 2 120μm 0.85 1.13 Example 3 120μm 0.95 1.23 Example 4 120μm 0.87 1.15 Comparative Example 1 120μm 0.35 0.486 Comparative Example 2 120μm 0.12 0.16
[0188] According to Table 1, the electrode film in the embodiment of the present application has excellent tensile force and strength, which indicates that the present application can significantly improve the tensile strength of the electrode film by selecting the composition and structure of the electrode film, thereby helping to extend the service life of the electrode;
[0189] In particular, it can be seen from Example 1 and Comparative Example 1 that when the active materials are all SiOx-C, the tensile force of the electrode membrane of the present application can be 2.3 times that of the electrode membrane in Comparative Example 1, and the strength of the electrode membrane of the present application can be 2.3 times that of the electrode membrane in Comparative Example 1, indicating that the present application can improve the strength of the electrode membrane by increasing the fiberization degree of the electrode membrane;
[0190] It can be seen from Example 2 and Comparative Example 1 that when the active site materials are all LFP, since the electrode membrane of the present application has a higher degree of fiberization, the tensile force of the electrode membrane of the present application can be 7.08 times the tensile force of the electrode membrane in Comparative Example 2, and the strength of the electrode membrane of the present application can be 7.06 times the strength of the electrode membrane in Comparative Example 2, indicating that the present application can improve the strength of the electrode membrane by increasing the degree of fiberization of the electrode membrane.
[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An electrode film, characterized in that: The electrode membrane comprises fibers, and the fiberization degree of the electrode membrane is 40-95%; Based on the total mass of the electrode film, the mass percentage of the binder is ≤2%.
2. The electrode film according to claim 1, characterized in that The electrode film also includes an active substance; The fibers include first fibers and second fibers, the first fibers have a length of an order of magnitude less than or equal to the particle size of the active material, and the second fibers have a length of an order of magnitude greater than the particle size of the active material.
3. The electrode film according to claim 2, characterized in that: The amount percentage of the first fibers in the fibers is 5-50%.
4. The electrode film according to claim 2 or 3, characterized in that: The length of the first fiber is 0.3-10 μm; And / or, the second fibers have a length of 50-300 μm.
5. The electrode film according to any one of claims 2 to 4, characterized in that: The diameter of the first fiber and / or the second fiber is 60-150 nm.
6. The electrode membrane according to any one of claims 2 to 5, characterized in that: The thickness of the electrode film is 110-2000 μm.
7. The electrode membrane according to any one of claims 2 to 6, characterized in that: The active material is selected from at least one of carbon materials, metal platinum, silicon-carbon materials, lithium iron phosphate materials, positive electrode ternary materials, silicon-oxygen materials, lithium cobalt oxide, lithium manganese oxide and lithium titanate.
8. The electrode film according to claim 7, characterized in that The length of the first fibers is 0.3-3 μm, 0.3-5 μm, 5-10 μm or 3-10 μm.
9. The electrode film according to claim 7 or 8, characterized in that: The length of the second fibers is 50-200 μm, 100-150 μm, 150-200 μm or 200-300 μm.
10. The electrode membrane according to any one of claims 7 to 9, characterized in that: The thickness of the electrode film is 110-500 μm, 110-300 μm, 100-350 μm, 110-500 μm, 500-800 μm, 500-1000 μm or 1000-2000 μm.
11. The electrode membrane according to any one of claims 1 to 10, characterized in that: The fiberization degree of the electrode membrane is 60-90%, 50-70%, 70-95% or 40-60%.
12. The electrode membrane according to any one of claims 1 to 11, characterized in that: Based on the total mass of the electrode film, the mass percentage of the binder is 1%, 1.3%, 1.5%, 1.8% or 2%.
13. A method for preparing an electrode film according to any one of claims 1 to 12, characterized in that: include: The raw material system including the conductive agent, the binder and the active material is sequentially subjected to premixing treatment, shearing treatment and roll pressing treatment to obtain the electrode film; Wherein, in the raw material system, the mass percentage of the binder is ≤2%, and the binder includes a fibrillable binder; In the premixing process, the speed is 1000-3000 r / min, the temperature is 18-30° C., and the time is 2-60 min; In the shearing treatment, the rotation speed is 5000-7000 r / min, the temperature is 10-90° C., and the time is 5-90 min.
14. An electrode, characterized in that: The invention comprises the electrode membrane according to any one of claims 1 to 12.
15. An electrochemical device, characterized in that: Comprising the electrode according to claim 14.
16. An electronic device, characterized in that: The driving source or energy storage source of the electronic device includes the electrochemical device according to claim 15.
Citation Information
Patent Citations
Dry-method electrode film and preparation method and application thereof
CN113871566A
Process of making PTFE fibers
US5686033A